2019
DOI: 10.3389/fpsyg.2019.01161
|View full text |Cite
|
Sign up to set email alerts
|

Picture This: A Review of Research Relating to Narrative Processing by Moving Image Versus Language

Abstract: Reading fiction for pleasure is robustly correlated with improved cognitive attainment and other benefits. It is also in decline among young people in developed nations, in part because of competition from moving image fiction. We review existing research on the differences between reading or hearing verbal fiction and watching moving image fiction, as well as looking more broadly at research on image or text interactions and visual versus verbal processing. We conclude that verbal narrative generates more div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 214 publications
(251 reference statements)
0
4
0
1
Order By: Relevance
“…For example, cognitive processing of images was found to be much faster and automatic compared to the slower and more controlled processing of printed text (Jabr, 2013;Powell et al, 2019). Likewise, a review of research comparing the processing of verbal and non-verbal narratives vs. moving images found viewing and reading narratives have different cognitive loads, with the former requiring greater cognitive investment (Jajdelska et al, 2019). As Greenfield (2009) sums up related research, 'reading is associated with reflection, television is associated with impulsivity' (p. 71).…”
Section: Educational Television and Associated Cognitive Processesmentioning
confidence: 99%
“…For example, cognitive processing of images was found to be much faster and automatic compared to the slower and more controlled processing of printed text (Jabr, 2013;Powell et al, 2019). Likewise, a review of research comparing the processing of verbal and non-verbal narratives vs. moving images found viewing and reading narratives have different cognitive loads, with the former requiring greater cognitive investment (Jajdelska et al, 2019). As Greenfield (2009) sums up related research, 'reading is associated with reflection, television is associated with impulsivity' (p. 71).…”
Section: Educational Television and Associated Cognitive Processesmentioning
confidence: 99%
“…In contrast, watching video is a more passive process due to the fact that there is less scope for personal interpretation. Indeed, Jajdelska et al 11 recently reviewed a wide field of evidence investigating the differences between narrative processing of spoken or written stories, and moving images. They concluded that, 'verbal narrative generates more diverse responses than moving image narrative, ' and recommend that future research focuses on differences in neural mechanism between the two.…”
mentioning
confidence: 99%
“…We removed the audio and edited some of the videos slightly to adjust the length (which varied from 57 to 63 s). We selected non-verbal narratives in video format because motion picture narratives are less susceptible to interindividual differences and generate more homogeneous experiences across individuals than verbal (oral) narratives ( Jajdelska et al, 2019 ). This may be because the visual images are directly related to the narrative content, which reduces personal interpretations of the story ( Richardson et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%